Luminescence modification of CsI crystal activated by CsCI impurity - Voloshinovskii, A.; Myagkota, S.; Chornodolsky, Ya.; Stryganyuk, G. (Functional Materials, 2007)
Luminescence parameters of CSI-CsCI (0.5-1.0 mol.%) and CsI-PbCI₂ (0.5 mol.%) crystals have been studied under synchrotron and X-ray excitation. New bands have been reavealed in the luminescence spectra of crystals wich are ascribed to emission of microphase CsCI dispersed in CsI and radiative decay of electronic excitation on iodine vacancies of the matrix. The duration and intensity of slow component in a scintillation pulse of CsI-PbCI₂ (0.5 mol.%) crystals decreases essentially at the X-ray excitation.